The difference of information diffusion for Seoul tourism destination according to user certification on Sina Weibo: through data crawling method. Issue 4 (2nd October 2017) - Hlee, Sunyoung; Cheng, Ao; Koo, Chulmo; Kim, Taekyung
Abstract: Consumer's information search and sharing behaviour is critical to firm's stratigic decision-making in SNS tourism marketing. Although there are many studies on SNS marketing, unlike previous research, our empirical study investigates the relationship between user certification and information elaboration degrees on Sina Weibo. Tourism information diffusion is used as an indication of rationality in order to provide a test to the explanation of consumer behaviour towards 'Repost' and 'Like'. To understand this phenomenon, we collected data from Sina Weibo with a data harvesting programme. After filtering data, anlaysis was carried out on 5746 units. Espeically, we focused on 'Seoul', one of the biggest cities in Asia for wanna-visit tour destination. The focus of this study is the two types of user certification (official vs. personal) in concept of a rational information search and the moderating role of information elaboration level. To verify hypotheses, the Poisson Regression Method was applied. Empirical results indicated that 'information shoppers' for tourism purpose would react differently by information source certifications. Consumers are less likely to share 'Like' count generated by an official verified user when content elaboration level is relatively high. To the contrary, for a personal certification user, people are less likely to repost under high elaboration.